Content Analysis of Vocabulary Materials on English Textbook at 10th Grade - Mentari Florentina Pasaribu; Siti Wina Putri Lubis; Mei Melawati Siagian; Sri Previna; Erikson Saragih (Yavana Bhasha : Journal of English Language Education, 2020)
The purpose of this study was to analyze the vocabulary material in 10th grade English books in secondary schools published by the Ministry of Education and Culture. This research was conducted by solving three problems namely; what topics are available in grade 10 English textbooks; how vocabulary topics are presented; and why vocabulary content is important to discuss. The design of this study is descriptive analysis with book instruments as data sources and English teacher interviews. The books analyzed consist of fifteen chapters, and each chapter provides vocabulary content. The results of this study were conducted with the vocabulary analysis criteria suggested by Celce Murcia and showed that the vocabulary contained in the textbook contained more vocabulary that was appropriate to the topic and learning objectives than vocabulary that did not fit the topic. and from the research that has been done, there are results that the inclusivity criteria per syllabus get the highest value, 3.8; accessibility criteria with a value of 3.5; the average value can be in the context of the criteria of suitability, the suitability of the load, and balanced distribution. The interview also showed that vocabulary is very important to discuss because, without vocabulary, students' ability to communicate cannot occur properly and correctly.